Current-mode KHN biquad filter using modified CFTAs and grounded capacitors - Satansup, Jetsdaporn; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2011)
In this paper, a current-mode Kerwin-Huelsman-Newcomb (KHN) filter structure employing four modified current follower transconductance amplifiers (MCFTAs) and two grounded capacitors is proposed. The circuit structure has one low-impedance current input and three high-impedance current outputs, and enables realizing lowpass, bandpass and highpass current responses simultaneously. The bandstop and allpass responses can also be obtained by connecting appropriate output currents directly without additional devices. The proposed filter is capable of providing an independent current-control of the natural angular frequency (ω0) and quality factor (Q) through the transconductance of the MCFTA. Moreover, high-Q value filter can be realized by simply tuning the ratio of MCFTA's transconductance. To support the theoretical results, the properties of the presented filter have been verified by simulation results.
Keywords: Biquad filter; Current Follower Transconductance Amplifier (CFTA); Current-mode circuit; Kerwin-Huelsman-Newcomb (KHN)